The Ch'ixi Methodology in Antiperformance: Palimpsest - Pacahuala Mallqui, Juliet Rashell (2024)
This article focuses on the process of the scenic composition of the project Antiperformance: Palimpsest through the ch'ixi as a performative methodology. The ch'ixi refers to the power in permanent contradiction (Rivera, 2018) confronting the dichotomous and static worldview of the colonial western tradition. For this reason, Rivera Cusicanqui proposes the ch'ixi gaze as an approach that invites the colonized subject to assume the multiple contradictions he/she inhabits. In relation to this anticolonial approach, a methodology is proposed in the performing arts to approach an anticolonial performance, as a praxis focused on corporealities that alter their colonized gaze. For this, the taypi or “ch'ixi space” (Rivera Cusicanqui, 2023) is recognized as indispensable to understand what happens during the contact of perpetual contradictions that detonate the critical energy necessary for a new sensoperceptive gaze in the movement of each corporeality, in this way the scenic space in the anticolonial performance is understood in the logics of the taypi. The objective of this article is to validate the ch'ixi methodology as a paradigm that links western and indigenous scenic knowledge, recognizing its relevance in the processes of artistic creation, developing new ways of perceiving the scenic-performance composition.